2019
DOI: 10.1115/1.4042529
|View full text |Cite
|
Sign up to set email alerts
|

Performance Effects of Leading Edge Tubercles on the NREL Phase VI Wind Turbine Blade

Abstract: Several studies on wind energy have been conducted to find possible solutions to power issues related to the variable nature of the wind. One of the most promising seems to be the application of sinusoidal modifications (tubercles) on the leading edge of wind turbine blades. In the present work, a systematic study on the effects of different tubercle configurations on NREL phase VI wind turbine performance is conducted. A design of experiments is used to generate blades with different tubercle amplitude and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Whereas Abate et al [9], and Lohry et al [11] results have an agreement with the study's optimum configuration, Hansen et al [3], and Paula et al [12] obtained a different optimum configuration of small amplitude and small wavelength.…”
Section: M39mentioning
confidence: 59%
See 2 more Smart Citations
“…Whereas Abate et al [9], and Lohry et al [11] results have an agreement with the study's optimum configuration, Hansen et al [3], and Paula et al [12] obtained a different optimum configuration of small amplitude and small wavelength.…”
Section: M39mentioning
confidence: 59%
“…Abate et al [9] tested the performance of wind turbines with different tubercles configurations and their effect on power and annual energy production. Abate et al [9] found a considerable improvement for all tubercles configurations in high wind speeds and stall conditions. At low speed, tubercles degraded the wind turbine performance.…”
Section: M22mentioning
confidence: 99%
See 1 more Smart Citation
“…Although high wind speeds (more than 15 m/s) are often characterized by unsteady phenomena, the unsteady behavior of localized vortices has very little bearing on the overall aerodynamic performance of wind turbine blades [61]. The analysis is consequently conducted using stable Reynolds Averaged Navier-Stokes (RANS) Equations with the k-ω SST turbulence model, where convergence is obtained for all the simulations with an error of 10 −4 .…”
Section: Mesh Topology and Grid Independence Investigationmentioning
confidence: 99%
“…In contrast, it is easier to realize the passive methods to change the characteristics of the main flow by adding auxiliary components on the external surface and mixing the airflow of the components with the main flow. For example, tip winglets [7][8][9][10], bionic leading edges [11][12][13], Gurney flaps [14][15][16], vortex generators [17][18][19][20][21][22][23][24], and other components have been added to the blades to improve the wind turbine's aerodynamic performance. Nobari et al [7] studied a wind turbine equipped with flat winglets by the finite volume method, and the wind turbine power increased by 16% after optimization.…”
Section: Introductionmentioning
confidence: 99%